1975
DOI: 10.1136/thx.30.4.447
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative autologous blood transfusion: report of a technique.

Abstract: . (1975). Thorax, 30,[447][448][449][450][451] Intraoperative autologous blood transfusion: report of a technique. Using a simple and relatively inexpensive technique, blood was salvaged during major thoracic and cardiovascular surgery in 34 cases. Detailed haematological, biochemical, and bacteriological studies were carried out, with red cell survival studies. It has been shown that cellular as well as non-cellular elements of the blood were well preserved with little or no bacterial contamination. It has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Previously a few authors have cultured circulating venous blood during autologous transfusion and have reported it to be sterile. Khan & Bassett (1975) cultured blood directly from the collecting bottle and recovered skin saprophytes in most cases from a pericardial blood pool. The present report is the first to quantify the degree of contamination by bacterial counting.…”
Section: Discussionmentioning
confidence: 99%
“…Previously a few authors have cultured circulating venous blood during autologous transfusion and have reported it to be sterile. Khan & Bassett (1975) cultured blood directly from the collecting bottle and recovered skin saprophytes in most cases from a pericardial blood pool. The present report is the first to quantify the degree of contamination by bacterial counting.…”
Section: Discussionmentioning
confidence: 99%
“…4 Various techniques have been employed for collection, filtration and transfusion of salvaged blood. 7 A successful case of retransfusion of salvaged blood using a simple technique is reported.…”
mentioning
confidence: 99%